(untitled) (CIPEEX, 2024)
The Brazilian Federal Constitution provides for the social right to physical and economic access to adequate and healthy food. In view of this, the importance of promoting awareness about healthy eating for children is evident, since adequate nutrition during childhood contributes to physical growth, cognitive development and establishes fundamental bases for health throughout life. METHODOLOGY: This study was carried out through an educational action, in the city of Anápolis, with the objective of raising awareness in early childhood about the importance of eating adequately and healthily. The action arose with the purpose of teaching children ways to achieve a balanced, sustainable diet according to the particular needs of each individual. The project took place in May 2024, at the Deputado José de Assis Municipal School, in the Lourdes neighborhood, in the city of Anápolis, in Goiás, with children between 6 and 7 years old, in the second year of elementary school. RESULTS: The project was planned and implemented in conjunction with students and faculty from the second semester of the medical course at the Evangelical University of Goiás. We addressed the topic of healthy eating, which is closely related to health in the sense of preventing various diseases and providing well-being. After a previous presentation of the topic emphasizing the importance of healthy foods and their benefits, an activity was carried out in which children had to paint pictures of foods and then place them in cardboard boxes with happy “faces” (healthy foods) and sad ones (unhealthy foods). In addition to the participation of the children, engagement was also noted among the faculty members present, who, as reported in a document delivered to them, 100% considered the theoretical presentation and proposed activities to be extremely relevant content, both for the postgraduate students and for the faculty, who are now better equipped to pass on this knowledge. CONCLUSION: In short, the activity achieved the proposed objective of educating and encouraging students to develop healthier eating habits. It is hoped that this experience report will inspire students and teachers to continue and also expand this project beyond the classroom, for example, by promoting cooking workshops that teach how to make healthy foods, and also through the construction of school gardens carried out in a way that fully involves students, with the aim of ensuring that such benefits for the school community are continuous and significant.